Creation of a pilot for the FlexOffer concept - Santos, Joss dos (2017)
The revolution in the energy market and the end user need to control the things he has around him lead to the creation of a new concept: flexoffers. The flexoffer is built around scheduling energy usage with the prices of the energy market. The flexoffer is comprised of the pattern of usage and a window of when the pattern can begin. Those parameters are exposed to the energy markets using an Aggregator, entity responsible for gathering all the flexoffers in a region. The market will reply to the flexoffer proposition with the best time for the consumption of that energy, which in this case is when the prices are the lowest. This project revolves around the implementation of a pilot capable of applying that concept to a real life situation. Thus FlexHousing was created. It allows for the control of the energy usage of the appliances in a home or building. Such is possible by the integration of external technologies. Virtual Power Solutions, a national energy solutions company developed a product called Cloogy. The Cloogy is a gateway installed in one’s house and is capable of communicating with smart device provided by VPS. In this case, smart plugs were deployed. These smart plugs are placed between the appliance and the electrical outlet. From there the plug is able to control the flow of electricity towards the appliance. Sensors are also installed in these plugs, capable of collecting data regarding the energy usage amongst other metrics. In order to operate the plugs, VPS also provided us with an external API, capable of receiving request and forwarding those request back to the plugs. FlexHousing is comprised of 2 modules: the FlexHousing middleware and the FlexHousing FrontEnd. The middleware acts as a hub for every operation in the FlexHousing environment. It bridges the various system in play, the flexoffer services and the VPS services. FlexHousing allows for the creation of rooms and the attachment of devices equipped with VPS technology. The user is then able to perform a variety of operations, such as, applying flexoffers, remotely controlling the appliances and collect data from the sensors in the VPS devices. For the interaction with the user, FlexHousing FrontEnd was developed. It provides a user-friendly graphical interface for the user to setup and control FlexHousing middleware. The interface revolves around the rooms and the devices. The user is able to check the flexoffers he has applied and the schedules the flexoffers services sent back. If the user wants, he can deploy the VPS smart plugs to non flexoffer complaint devices, such as lamps, television and computer. Using the FrontEnd, he is also capable of using them.